Human Rabies: A Reemerging Disease in Costa Rica? - Badilla, Xiomara (Centers for Disease Control and Prevention, 2003)
Two human rabies cases caused by a bat-associated virus variant were identified in September 2001 in Costa Rica, after a 31-year absence of the disease in persons. Both patients lived in a rural area where cattle had a high risk for bat bites, but neither person had a definitive history of being bitten by a rabid animal. Characterization of the rabies viruses from the patients showed that the reservoir was the hematophagous Vampire Bat, Desmodus rotundus, and that a sick cat was the vector.